Keep Calm and Carry on: Parental Opinions on Improving Clinical Dietary Trials for Young Children - Nicholl, Analise; O’Sullivan, Therese A. (Nutrients, 2018)
Recruitment can be an issue for paediatric research. We aimed to investigate parental opinions of paediatric clinical assessments, and to combine findings with recent literature to inform the design of a clinical dietary trial. We used convenience sampling to recruit 17 parents of children aged 2–6 years from two community playgroups in Perth, Western Australia. Three focus groups considered proposed child assessments, study design, and potential study enrolment. Qualitative thematic analysis of focus group transcripts used NVivo 11 (QSR, Melbourne, VIC, Australia). Four main parental concerns emerged, presented here with solutions combining parent responses and relevant literature. (1) Parent and child needle fear: a good experience and a good phlebotomist help keep participants calm, and offering additional analysis (e.g., iron status) makes blood tests more worthwhile. (2) Concerns about children’s age, stage, understanding and ability to cope: create a themed adventure to help explain concepts and make procedures fun. (3) Persistent misunderstandings involving study purpose, design, randomization and equipoise: provide clear information via multiple platforms, and check understanding before enrolment. (4) Parental decisions to enrol children focused on time commitment, respectful treatment of their child, confronting tests and altruism: child-centred methodologies can help address concerns and keep participants engaged throughout procedures. Addressing the concerns identified could improve participation in a range of paediatric health interventions.